2019
DOI: 10.1038/s41598-019-54575-3
|View full text |Cite
|
Sign up to set email alerts
|

Diagnostic performance of hematological discrimination indices to discriminate between βeta thalassemia trait and iron deficiency anemia and using cluster analysis: Introducing two new indices tested in Iranian population

Abstract: Although the discrimination between β-thalassemia trait (βTT) and Iron deficiency anemia (IDA) is important clinically, but it is challenging and normally difficult; so if a patient with IDA is diagnosed as βTT, then it is deprived of iron therapy. This study purpose was to evaluate the 26 different discriminating indices diagnostic function in patients with microcytic anemia by using accuracy measures, and also recommending two distinct new discriminating indices as well. In this study, 907 patients were enro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
13
0
2

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 26 publications
(16 citation statements)
references
References 46 publications
1
13
0
2
Order By: Relevance
“…From the research conducted, it was found that there were significant differences between hemoglobin levels, MCV values, RDW values, Mentzer Index and ferritin levels in iron deficiency anemia patients with beta minor thalassemia patients. This is in line with previous studies that conducted research on the use of a new index for hematological parameters to differentiate cases of iron deficiency anemia from cases of beta minor thalassemia 17 . levels between patients with iron deficiency anemia and beta minor thalassemia patients with p values <0.001.…”
Section: Discussionsupporting
confidence: 91%
“…From the research conducted, it was found that there were significant differences between hemoglobin levels, MCV values, RDW values, Mentzer Index and ferritin levels in iron deficiency anemia patients with beta minor thalassemia patients. This is in line with previous studies that conducted research on the use of a new index for hematological parameters to differentiate cases of iron deficiency anemia from cases of beta minor thalassemia 17 . levels between patients with iron deficiency anemia and beta minor thalassemia patients with p values <0.001.…”
Section: Discussionsupporting
confidence: 91%
“…The results found significant differences between, hemoglobin levels, MCV values, MCH values, ferritin levels between patients with iron deficiency anemia and minor beta thalasemia patients with a p<0.001 value. However, there was no significant difference between the RDW value of patients with iron deficiency anemia and minor beta thalasemia patients with a value of p=0.94 17 .…”
Section: Disscusionmentioning
confidence: 71%
“…The data analysis was conducted on 42 patients with a male gender of 4 (9.5%) with an average age of 17 Median hemoglobin (Hb) levels of iron deficiency anemia and thalasemia were found to be 9.60% and 9.80% (p 0.0037). Median MCV value and mentzer index of minor beta thalassemia patients were lower than iron deficiency anemia (61.59; 12.30) while the median RDW value of thalasemia patients was higher (16.60).…”
Section: Resultsmentioning
confidence: 99%
“…However, anemia can occur every trimester in pregnancy (Paendong, Suparman, and Tendean, 2016;Amini, Pamungkas, and Harahap, 2018). (Jahangiri, Rahim and Malehi, 2019). Low sensitivity means that the index is not capable enough to classify pregnant women as a Thalassemia carrier (Parikh et al, 2008).…”
Section: Abstrakmentioning
confidence: 99%